IMPLEMENTASI KEBIJAKAN PENATAAN PEDAGANG KAKI LIMA (PKL) DI KOTA SERANG - M Irfan; Nia Kania Kurniawati; TB Ace Hasan Syadzily (http://jurnal.untirta.ac.id/index.php/JIPAGS, 2018)
This research is motivated by the grow number of street vendors (PKL) in Serang City who used sidewalks, roads and other public facilities to become a selling place which are not intended. The purpose of this research is to find out how big is the Implementation of Policy of Structuring of Street Vendors in Serang City. Data collection techniques in the form of questionnaires based on the George Edward III’s Policy Implementation theory that consists of communication, resources, disposition, and bureaucratic structure. The method used in this research is quantitative by taking samples as much as 90 street vendors using Taro Yamane formula. From the discussion, it can be concluded that Implementation of the Policy of Structuring of Street Vendors in Serang City reached 57.70%. This proves that the implementation of the policy of structuring street vendors in Serang City has not been running well. The suggestion of this research is to provide an adequate and strategic location for street vendors as well as complete socialization to street vendors and the community about the policy of structuring of street vendors.